BioprospecÃÃo de compostos isolados de Combretum fruticosum com potencial antiproliferativo em cÃlulas tumorais in vitro - Andrea Felinto Moura (2015)
The use of substances from natural products has grown over the years, being the basis of therapeutic products. Lignans are molecules with large pharmaceutical use, which has aroused interest in search of new drugs to treat diseases. Much interest has been focused on their effectiveness as an antineoplastic agent. Thus, the aim of this study was to evaluate the in vitro anticancer potencial of compounds isolated from ethanolic extract of Combretum fruticosum, as well as, to study the possible mechanisms of action of a dibenzylbutyrolactone type lignan, trachelogenin, in colorectal cancer cells. The fractionation of the ethanolic extract of C. fruticosum resulted in the isolation of seven compounds: three triterpenes, two mixtures of β-sitosterol and stigmasterol steroids and two lignans Among them, the lignan, trachelogenin showed higher cytotoxic activity, with IC50 values ranging from 0.8 to 32.4 ÂM in glioblastoma (SF-295) and leukemic (HL-60) cells, respectively. While in normal cells (3T3-L1 and PBMC cells) the IC50 values were greater than 64.3 ÂM. The antiproliferative profile of different times of incubation was performed in SF-295 and HCT-116 cells. The cytotoxic effect on SF-295 cells was only observed after 72 hours of incubation, whereas in HCT-116 cells, this effect was observed after 48 hours, and it was enhanced after 72 hours of incubation. Before these results, analyzing cell cycle profile, membrane integrity, phosphatidylserine externalization and expression of proteins related to cell death by apoptosis in HCT-116 cells, it was not observed significantly changed, suggesting that the antiproliferative effect of this lignan is not related to mechanisms of cell death such as apoptosis and/or necrosis. Autophagy seems to be one of the cell death mechanisms involved in the antiproliferative effect of trachelogenin, because we observed an increase on number and size of acidic vesicular organelles (AVO) as well as the expression of proteins recruited during autophagy (LC3 A and B-II and Beclin-1) in cells treated with trachelogenin, although this seems not to be the only process involved. Therefore, we conclude that trachelogenin showed potent antitumor activity in vitro, and this effect may be related to the induction of autophagy. However, further tests should be conducted to confirm these proposals and to evaluate its mechanism of action and the therapeutic potential of this molecule better.